The Effect of Invigoration Using Polyethylene Glycol And Ultra Fine Bubble on Improving of Sengon Seeds (Falcataria Moluccana Miq.) Quality After Two Years Storage - Iskandar, Iskandar Z Siregar; Riki, Riki Ramdhani; Evayusvita , Evayusvita Rustam; Dede , Dede J Sudrajat (Jurnal Wasian, 2021)
Utilization of seeds storage results in decreased plant productivity. The increase can be used by treating seeds before planting through the technique of invigoration. This purpose of the study is to assess the effectiveness of invigoration methods using polyethylene glycol (PEG 6000) and ultrafine bubbles (UFB) to improve viability and vigor of sengon seeds (Falcataria moluccana). Seed agieng using 96 % ethanol was carried out to obtain the diversity of seedlot viability as the materials for testing the effectiveness of invigoration treatments. A complete random design was used to test the effectiveness of 5 invigoration treatments, i.e., seed without invigoration treatment, soaking in PEG 6000 -0.8 MPa, soaking in PEG 6000 -1.2 Mpa, soaking in UFB water injected by environmental air, and soaking in UFB water injected by oxygen 99 %, with soaking time is 24 hours for each treatment. Seed agieng resulted three classes of seed viability, i.e. 62 % (initial seed), 83 % (seed agieng for 30 minutes) and 57 % (seed agieng for 60 minutes). In the condition of seed germination before treatment (DBA) 57 % and DBA 62 %, invigoration treatments were significantly affected on seed germination capacity, but not significantly different in DBA 83 %. The soaking treatment of UFB injected by oxigen 99 % was able to improve the germination parameters (germination capacity, germination rate, and vigor index) on the sengon seeds with DBA 57 %. For seeds with DBA 62 %, the soaking treatment in UFB injected by environmental air was provided the best germination capacity, T50, and vigor index. The treatment of UFB injected by oxygen 99 % was more effective to improve the seed with very low viability and vigor (DBA 57 %). In general, improving of seed viability and vigor is more effective by using UFB than PEG 6000.